A Model for the Biosynthesis and Transport of Plasma Membrane-Associated Signaling Receptors to the Cell Surface - Popescu, Sorina C. (Frontiers in Plant Science, 2012)
Intracellular protein transport is emerging as critical in determining the outcome of receptor-activated signal transduction pathways. In plants, relatively little is known about the nature of the molecular components and mechanisms involved in coordinating receptor synthesis and transport to the cell surface. Recent advances in this field indicate that signaling pathways and intracellular transport machinery converge and coordinate to render receptors competent for signaling at their plasma membrane (PM) activity sites. The biogenesis and transport to the cell surface of signaling receptors appears to require both general trafficking and receptor-specific factors. Several molecular determinants, residing or associated with compartments of the secretory pathway and known to influence aspects in receptor biogenesis, are discussed and integrated into a predictive cooperative model for the functional expression of signaling receptors at the PM.